In-situ biophysical characterization of high-concentration protein formulations using wNMR - Jing Song; Marc Taraban; Y. Bruce Yu; Lynn Lu; Pallavi Guha Biswas; Wei Xu; Hanmi Xi; Akhilesh Bhambhani; Guangli Hu; Yongchao Su (Taylor & Francis Group, 2024)
ABSTRACTHigh-concentration protein formulation is of paramount importance in patient-centric drug product development, but it also presents challenges due to the potential for enhanced aggregation and increased viscosity. The analysis of critical quality attributes often necessitates the transfer of samples from their primary containers together with sample dilution. Therefore, there is a demand for noninvasive, in situ biophysical methods to assess protein drug products directly in primary sterile containers, such as prefilled syringes, without dilution. In this study, we introduce a novel application of water proton nuclear magnetic resonance (wNMR) to evaluate the aggregation propensity of a high-concentration drug product, Dupixent® (dupilumab), under stress conditions. wNMR results demonstrate a concentration-dependent, reversible association of dupilumab in the commercial formulation, as well as irreversible aggregation when exposed to accelerated thermal stress, but gradually reversible aggregation when exposed to freeze and thaw cycles. Importantly, these results show a strong correlation with data obtained from established biophysical analytical tools widely used in the pharmaceutical industry. The application of wNMR represents a promising approach for in situ noninvasive analysis of high-concentration protein formulations directly in their primary containers, providing valuable insights for drug development and quality assessment.